Genome-Wide Identification and Expression of Neuropeptides and Their Expression Patterns After RNAi of CHH Genes in Pacific White Shrimp Litopenaeus vannamei - Long Zhang; Lichao Sun; Guanghao Song; Beibei Wang; Yanting Cui; Fei Liu; Yuquan Li; Zhongkai Wang (Biology)
Neuropeptides are pivotal in regulating a broad spectrum of developmental, physiological, and behavioral processes throughout the life cycle of crustaceans. In this comprehensive study, we utilized a multiomics approach to characterize neuropeptide precursors and to assess the expression profiles of neuropeptide-encoding genes across various tissues and developmental stages in the Pacific white shrimp, Litopenaeus vannamei. Additionally, we explored the differential expression of neuropeptide genes in the eyestalk before and after the RNA interference-mediated suppression of crustacean hyperglycemic hormone (CHH) and vitellogenesis-inhibiting hormone (VIH) gene expression. Our study identified a total of 125 neuropeptide-encoding genes in L. vannamei, with 54 of these genes previously uncharacterized in the genome. Notably, certain neuropeptide-encoding gene families showed significant expansion, as demonstrated by the discovery of 10 adipokinetic hormone/corazonin-like peptide (ACP) genes, 55 CHH superfamily genes, and 13 pigment-dispersing hormone (PDH) genes. Alternative splicing was also found to play a crucial role in generating functionally diverse neuropeptides; for example, the agatoxin and calcitonin genes undergo alternative splicing that leads to the production of three distinct agatoxin neuropeptides and two distinct calcitonin neuropeptides, respectively. Neuropeptide genes are predominantly expressed in neuroendocrine tissues, including the eyestalk, cerebral ganglia, thoracic ganglia, and ventral ganglia. During the embryonic development of L. vannamei, with the exception of the molt-inhibiting hormone (MIH) gene, all monitored genes display minimal expression from the zygote stage through to the larval in membrane (Lim) stage. In contrast, the majority of these genes exhibit a steady uptick in expression from the nauplius stage onwards, culminating in the post-larval stage. Furthermore, comparative transcriptomic analysis of the eyestalk revealed that the expression of the majority of neuropeptide genes was downregulated following the suppression of CHH and VIH gene expression. This downregulation was significantly associated with the enrichment of pathways related to amino acid metabolism and hormone synthesis. The findings of this study provide valuable insights for future research aimed at elucidating the role of neuropeptides in regulating physiological functions in L. vannamei, potentially leading to advancements in shrimp aquaculture practices.